The Effect of Income Changes on Consumer Preferences for Two?Wheeler Vehicles in India - Dash, Prasanta Kumar (Journal of Global Economy, Business and Finance, 2026)
In this paper we try to put the relationship between income changes and consumer choices, focusing on the dynamic nature of consumer behaviour in response to fluctuations in personal finances and economy. Income, being a central determinant of an individual's purchasing power, plays a pivotal role in shaping the consumption patterns and preferences of consumers. In this study, we explore customer purchasing thought process as well as their likes and dislikes for and tastes in the leading brands in India's two wheeler market. Consumer behaviour toward brand names that are more valued in conventional markets changes as income levels do. We capsulate how various two wheeler brand environments in conventional retailers might differentially impact customer decisions in order to answer these and related problems. Also we put forward the imperial changes in two wheeler market pre and post covid phase. How the rising brand rises more height of sale irrelevant to the pandemic period as customer choice. Brand names become more significant in various categories based on the amount of information available to consumers. As a result, the study's main objective is to investigate the brand preferences of the public. The investigation is then conducted using a data analysis method. This study synthesizes existing research and empirical evidence to provide a comprehensive analysis of how income changes influence consumer choices in various economic contexts.